2010
DOI: 10.1121/1.3466875
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic predictors of upcoming positive or negative content in spoken messages

Abstract: This article examines potential prosodic predictors of emotional speech in utterances perceived as conveying that good or bad news is about to be delivered. Speakers were asked to call an experimental confederate to inform her about whether or not she had been given a job she had applied for. A perception study was then performed in which initial fragments of the recorded utterances, not containing any explicit lexical cues to emotional content, were presented to listeners who had to rate whether good or bad n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…They observed that acted emotions (especially negative emotions) were perceived more strongly than real ones hence questioning the usefulness of acted emotions. Moreover, the authors of [37,43,44] conducted perceptual tests for the recognition of various emotional expressions using visual imaging of speaker's face in the valence dimension. It was observed that the recognition speed was faster for positive emotions than for negative emotions, and also that acted emotions were perceived as more intense than true emotions [43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that acted emotions (especially negative emotions) were perceived more strongly than real ones hence questioning the usefulness of acted emotions. Moreover, the authors of [37,43,44] conducted perceptual tests for the recognition of various emotional expressions using visual imaging of speaker's face in the valence dimension. It was observed that the recognition speed was faster for positive emotions than for negative emotions, and also that acted emotions were perceived as more intense than true emotions [43].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors of [37,43,44] conducted perceptual tests for the recognition of various emotional expressions using visual imaging of speaker's face in the valence dimension. It was observed that the recognition speed was faster for positive emotions than for negative emotions, and also that acted emotions were perceived as more intense than true emotions [43]. In [35], authors used spontaneous expressive mono-word utterances and the corresponding acted utterances (collected simultaneously) for perceptual evaluation with native French listeners in audio-only, visual-only, and audio-visual data.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, using a preface may help to mitigate the telling of the negative news and to avoid a potential failure of the interaction [3]. Speakers may use prosody to signal in advance of upcoming emotional information [4]. In [4], an acoustic experiment tested whether speakers use prosody in prefaces ("We have had interviews last week") to signal the valence of upcoming news ("and I would like to inform you that we want to offer you the job").…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of work has been carried out so far on prosodic correlates of emotions, such as pitch, intensity, voice quality and speech rate [2,3] Research has also discussed such prosodic characteristics along two main dimensions organizing emotional responses, i.e., valence (the intrinsic attractiveness or aversiveness of an emotion) and arousal (a state of physiological activation, i.e., how intensely an emotion is felt). For instance, it has been found that prosodic characteristics can be used by listeners to predict whether the speaker is about to give a happy or sad news, even in absence of lexical information [4,5]. Based on the level of arousal, researchers have distinguished two main prosodic patterns [6].…”
Section: Introductionmentioning
confidence: 99%
“…The first pattern is characterized by high average of pitch, wide range and variability of pitch, high intensity and high speech rate, is typical of emotions with high arousal, like joy and anger. The second is characterized by low fundamental frequency, range and variability of intonation narrow, weak intensity and reduced speed, is typical of emotions with low arousal, like sadness [7,8,2,4]. It is possible that emotions which have the same level of arousal, share acoustic characteristics like pitch range and speech rate [9,7].…”
Section: Introductionmentioning
confidence: 99%